KARAKTERISTIK ORGANOLEPTIK DAN UJI KEBUSUKANDENGAN METODE UJI POSTMA ABON DAGING SAPI YANGDIBERI PENAMBAHAN BUAH KLUWIH (Artocarpus camansi) PADAKONSENTRASI BERBEDA. - Masyitah Masyitah; Zahrul Fuadi; M.Zoel Fahmi (Prodi Ilmu Peternakan Universitas Muhammadiyah Cirebon, 2026)
Abon is a type of processed dry food product with a distinctive shape made from meat that is boiled, shredded, seasoned, fried and then pressed. The addition of kluwihfruit (Artocarpus camansi) in shredded beef production may influence consumer acceptance. In addition to organoleptic evaluation, the product should also be assessed for the early stage of spoilage using the Postma test. The purpose of this study was to determine the organoleptics caracteristic and Postma test that were given the addition of kluwih fruit beef floss with diffrent cosentration. The research design used was a completely randomized design with 5 treatments and 3 replications. The treatments that were tried were, without the addition of kluwih fruit (T0), addition of kluwih fruit 5% (T1), addition of kluwih fruit 10% (T2), addition of kluwih fruit 15% (T3), and addition of kluwih fruit 20% (T4). The postma test showed negatif result for all treatmens, indicating that no early spoilage was detected in the shredded beef sample. Organoleptic evaluation revealed that the addition of kluwih fruit significantly affected (P<0,05) the taste aroma, and texture of shredded beef but had no significant effect on its color. The addition of kluwih fruit (Artocarpus camansi) in shredded beef production may influence panelists’s acceptance.